A digitial map of irrigated areas - An update for Asia - Siebert, Stefan; Feick, Sebastian; Hoogeveen, Jippe (., 2005)
Agriculture is by far the largest water-use sector, accounting for about 70 percent of all water withdrawn worldwide from rivers and aquifers for agricultural, domestic and industrial purposes. In several developing countries, irrigation represents up to 95 percent of all water withdrawn, and it plays a major role in food production and food security. The agriculture development strategies of most of these countries depend on the possibility of maintaining, improving and expanding irrigated agriculture. However, as the pressure on water resources increases, irrigation is facing growing competition from other water-use sectors and becoming a threat to the environment in an increasing number of regions. In the last decade, the international community has made major efforts to assess the different elements of the water balance and to predict current and future water needs for the different use sectors. However, considerable uncertainty remains concerning the extent and distribution of irrigated land in the world and on agricultural water use, therefore, making it difficult to monitor the irrigation sector adequately. Coverage of irrigated areas in the world, available in a geographical information system (GIS), is the single most important item of information needed to improve future global studies on water and food. The first version of the Digital Global Map of Irrigated Areas was published in 1999 (see table). It consisted of a raster map with a resolution of 0.5 ° by 0.5 ° containing the percentage of the area that was equipped for irrigation around 1995, the so-called irrigation density. To further develop and improve the global GIS coverage of areas equipped for irrigation and to make it available to users in the international community, cooperation was established between the Johann Wolfgang Goethe University in Frankfurt am Main, Germany, and the Land and Water Development Division of the Food and Agriculture Organization of the United Nations (FAO). Through this cooperation, the mapping project has been linked closely to the FAO global information system on water and agriculture, Aquastat. The Aquastat programme collects and disseminates data and information by country and by region. Its aim is to provide users interested in global, regional and national analysis (e.g. policy-makers, decision-makers and researchers) with the most accurate, reliable, consistent and up-to-date information available on water resources and agricultural water management. In order to make thorough analyses, the Aquastat programme collects data from many different sources including national water resources and irrigation master plans, statistics and yearbooks, FAO technical reports, and national and international surveys and reports made available by national and international research centres. The data collected through the Aquastat programme have served as the main source for improving the overall quality and resolution of the Digital Global Map of Irrigated Areas. In addition, the methodology for producing the map has been improved substantially. This has made it possible to increase the spatial resolution of the map to 5 minutes, thus justifying the publication of an improved second version of the Digital Global Map of Irrigated Areas. For Version 2, updated maps of Latin America, Europe, Africa and Oceania have been published. The next step in improving the dataset is the inclusion of the continent of Asia, which is presented in this document. For the update of the map of Asia, an inventory of subnational irrigation statistics for the continent was compiled. Irrigation maps were derived from project reports, irrigation subsector studies and books related to irrigation and drainage and were compared with satellite images in many regions. The reference year for the update of the map is 2000.
UnivIS-Import:2015-04-02:Pub.2005.nat.dgeo.IG.zentr.adigit_7
Keywords: data set; digital map; irrigation; hydrology; Asia